Electrochemical synthesis of manganese dioxide in the presence of ions Fe2+ and Co2+ - Сокольський, Г.В.; Іванова, Н.Д.; Іванов, С.В.; Болдирєв E.І.; Кобилінська, О.В.; Демченко, М.В. (Proceedings of National Aviation University (archive), 2009)
Manganese dioxide samples have been prepared by the anode deposition from fluoride containing electrolytes based on manganese sulphate at the presence of additives of iron(II), cobalt(II) ions. Obtained materials were characterised with AAS and DTA. The influence of doping by ions of iron(II) and cobalt(II) on the chemical composition of the samples obtained has been analysed.